Infalibilitas Paus dalam Perspektif Gereja Roma Katholik - Nur Fitriyana (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2013)
Dewan Vatikan pertama yang didominasi oleh tokoh-tokoh kepausan jelas merupakan suatu dewan kontroversi dalam Gereja Katolik, dan dalam hubungannya dengan gereja-gereja lain dan dunia yang lebih luas. Dewan menyatakan hal-hal yang tidak bisa diterima banyak orang; dan hal ini tampaknya menunjukkan bahwa Gereja Katolik memiliki sikap otoriter. Dewan Vatikan Pertama muncul oleh Norman P. Tanne yang masih menerjemahkan ajaran Katolik Roma dan tidak merasa perlu untuk pergi lebih jauh dari formatnya, terutama dalam perdebatan dengan gereja-gereja Protestan yang masih sangat banyak mengambil sikap untuk membela diri. Namun dalam domain lainnya telah banyak peristiwa. Tahun 1789 Revolusi Perancis dan Revolusi Industri yang dimulai pada akhir abad 18, menyebabkan perubahan besar dalam suasana politik, pembangunan sosial dan ekonomi di dunia Barat. First Vatican Council which is dominated by the definition of papal infallibility is definitely a council of controversy in the Catholic Church, and in conjunction with other churches and the wider world. Council states things that are not acceptable to many people and this event seems to show Catholic Church there at the height of aggressiveness and Authoritarian. First Vatican Council appeared startled by Norman P. Tanner (2003: 108) The Council of Trento apparently still provide the translation of Roman Catholic Theology adequately and does not feel the need to go further than his formulation, especially in the debate with Protestant churches are still very much taking attitude to defend themselves, other Council does not seem necessary. But in other domains has been a lot of events. 1789th French Revolution and the Industrial Revolution that began in the late 18 century, causing major changes in the political atmosphere, social and economic development in the Western world. The Enlightenment of the 18th century lead to a lot of intellectual challenge to the Christian faith and is complicated in the next century by advances in science that gives rise to further problems, such as the investigation of Darwin.